IKIGAI AMONG JAPANESE - Sazali, Noor Syahirah; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2024)
Ikigai is a combination of "iki" (生き), signifying life, and "kai" (甲斐), representing the realization of expectations and hopes. The emergence of this concept has proven to significantly contribute to a better lifestyle. This study aimed to explore the perception of personal ikigai and its institutionalisation. The results from the analysis of 5400 Japanese articles using Leximancer have shown a positive correlation between ikigai and one’s personal passions, meaning, and purpose. Beyond that, ikigai can also be perceived through contributing to others’ well-being. The study reveals ikigai’s dynamic adaptability to life’s challenges and its role in prompting a reevaluation of life purpose during significant events. This adaptive quality emphasises the resilience and relevance of ikigai in navigating the complexities of existence. Finally, institutions and community initiatives do help in fostering ikigai within communities.